Ladderane and lipid biomarker estimate of the sources and distributions of anammox activities in Laizhou Bay of the Bohai Sea, China - Shi, Mingwei; Xiao, Xiaotong; Ma, Haili; Li, Li; Wang, Yujue; Dong, Caixia; Ding, Yang; Zhao, Meixun (Frontiers in Marine Science, 2023)
Anaerobic ammonium oxidation (anammox) plays an important role in nitrogen removal in coastal seas, and ladderanes, as specific biomarkers of anammox bacteria, can be used to indicate the anammox activity. However, the origins of ladderanes and their controlling factors in the coastal seas influenced by anthropogenic activities are still not well constrained. To address this, we reported ladderanes, long-chain n-alkanols (terrestrial biomarker) and sterols (marine biomarker) in suspended particulates from the estuaries and inner area of Laizhou Bay in North China, to study ladderane sources and its distribution patterns. This study proposed a novel index, Rlad, using ladderane ratio of ladderane III to ladderane IV, and by correlating this index with other biomarker distributions to evaluate the source of ladderanes. High Rlad values (> 0.9) indicated biosynthesis by terrestrial anammox bacteria Ca. Brocadia and Ca. Kuenenia, while low Rlad values (< 0.9) indicated biosynthesis by marine anammox bacteria Ca. Scalindua. High Rlad values and high ladderane concentrations in particulates from the estuaries and nearshore area of Laizhou Bay revealed sources from the terrestrial input via riverine inflow as well as in situ production in oxygen-depleted estuaries, supported by high concentrations of terrestrial biomarkers; Low Rlad values and low ladderane concentrations in particulates from offshore area indicated sources from marine environment via the cold hypoxia water input by the Bohai circulation. Comparison of ladderane concentrations of our study with previously published results from a wide range of environments with human influences from Chinese coastal area revealed that high ladderane concentrations synthesized by terrestrial anammox bacteria could contribute significantly to coastal seas, and the anammox process in river-estuary-bay system might be underestimated. This study provides new understandings about the evaluation of the source and distribution of ladderanes under anthropogenic influences in coastal seas.